A Hydrostratigraphic Framework for the Paleozoic Bedrock of Southern Ontario - Carter, Terry R.; Fortner, Lee D.; Russell, Hazen A.J.; Skuce, Mitchell E.; Longstaffe, Fred J.; Sun, Shuo (Geoscience Canada, 2021)
Groundwater systems in the intermediate to deep subsurface of southern Ontario are poorly understood, despite their value for a number of societal uses. A regional hydrostratigraphic framework is a necessary precursor for improving our understanding of groundwater systems and enabling development of a 3-D hydrostratigraphic model to visualize these groundwater systems. This study is a compilation and integration of published and unpublished geological, hydrogeological, hydrochemical and isotopic data collected over the past 10 years to develop that framework. Bedrock is covered by a thin veneer of surficial sediments that comprise an aquifer/aquitard system of considerable local variability and complexity. Aquifers in the bedrock are thin and regionally extensive, separated by thick aquitards, within a well-defined lithostratigraphic framework and a well-developed hydrochemical depth zonation comprising a shallow fresh water regime, an intermediate brackish to saline sulphur water regime, and a deep brine regime of ancient, evaporated seawater. Occurrence and movement of groundwater in shallow bedrock is principally controlled by modern (Quaternary) karstic dissolution of subcropping carbonate and evaporite rocks, and in the intermediate to deep subsurface by paleokarst horizons developed during the Paleozoic. Flow directions in the surficial sediments of the shallow groundwater regime are down-gradient from topographic highs and down the regional dip of bedrock formations in the intermediate regime. Shallow karst is the entry point for groundwater penetration into the intermediate regime, with paleo-recharge by glacial meltwater and limited recent recharge by meteoric water at subcrop edges, and down-dip hydraulic gradients in confined aquifers. Hydraulic gradient is up-dip in the deep brine regime, at least for the Guelph Aquifer and the Cambrian Aquifer, with no isotopic or hydrochemical evidence of infiltration of meteoric water and no discharge to the surface. Fourteen bedrock hydrostratigraphic units are proposed, and one unit comprising all the surficial sediments. Assignment of lithostratigraphic units as hydrostratigraphic units is based principally on hydrogeological characteristics of Paleozoic bedrock formations in the intermediate to deep groundwater regimes, below the influence of modern meteoric water. Carbonate and evaporite rocks which form aquitards in the subsurface may form aquifers at or near the surface, due to karstic dissolution by acidic meteoric water, necessitating compromises in assignment of hydrostratigraphic units.